Psychometric validation of the continuum beliefs of mental illness scale (CB-MIS) and its associations with stigma - Lina-Jolien Peter; Thomas McLaren; Samuel Tomczyk; Holger Muehlan; Silke Schmidt; Georg Schomerus (BMC Psychiatry)
Abstract Background Continuum beliefs of mental health and illness are robustly negatively correlated with mental illness stigma. However, there is a lack of multidimensional and validated measures, not entirely relying on vignettes. Methods To develop such a scale, a pool of 37 items adapted from other studies on continuum beliefs, was initially examined in expert discussions and a convenience sample (N = 227, M age=32 years, 80.6% female). Items were selected based on theoretical tenability and assigned to pre-defined facets of “State”, “Person”, and nosological “Concept” in relation to mental illness. In a second sample (N = 1375; M age=42 years; 65.2% female), the Continuum Beliefs of Mental Illness Scale (CB-MIS) was psychometrically tested (i.e. factorial, convergent, discriminant validity). Results The scale comprises three subscales with three items, and one optional vignette-based item each, rated on a 5-point Likert scale. It showed very good factorial and discriminant validity, associations with stigma were moderately negative. The scale exhibited good test-retest reliability over a period of six months. Conclusions A validated, practical, multifaceted measure is offered to evaluate beliefs regarding the continuum of mental health and illness. Future studies should conduct subgroup-specific investigations regarding sociodemographic and illness variables, and could apply this measure to anti-stigma interventions. Trial registration German Clinical Trials Register: DRKS00023557. Registered 11/12/2020. World Health Organization, Universal Trial Number: U1111–1264–9954. Registered 16/02/2021.